Produção de biogás a partir da co-digestão anaeróbia de capim-elefante com vinhaça em reator em batelada - Silva, Olga Eliza Rocha e (2020)
SILVA, O. E. R. Biogas Production from anaerobic co-digestion of elephant grass and vinasse in batch reator. 2020. 73 f. Dissertation (master) – Postgraduate program in water resources and sanitation. Federal University of Alagoas, 2020. This study aimed to determine the production of biogas from the codigestion of elephant grass and vinasse. Elephant grass was tested in the form of broth, with COD concentration of 8534,21 mg/L. The elephant grass broth was mixed with vinasse, which presented 30.000 mg/L of COD, in different proportions %v/c ( A – 25/75; B – 50/50; C - 75/25, reactor D - 100/0, reactor E - 0/100). In addition, it was evaluated the effect of adding alkalinizer to the mixture which presented the higher methane production. The volume of the reactor was 106 mL. The codigestion yield of the biogas was evaluated for the mixing ratios and for each of the indicated substrates. The yield of accumulated methane production in values of 7,63 – 370,94 mLCH4/gSV and it was possible to verify the amount (%v/c) fo the B reactor (50/50) reached a higher methane production, reaching 370,94 mLCH4/gSV. In addition, it is assumed that from the results obtained, that codigestion increases the accumulated methane production of reactors by 97,8%, when compared to the best and previous reactors. Mono digestion did not show significant methane production, being worse than broth of elephant grass, that accumulated 7,3 mLCH4/gSV and the vinasse reached 88,335 mLCH4/gSV. These values were followed after 40 days of operation and recorded COD removal efficiencies of up to approximately 80%. Among the reactors tested, B reactor showed the highest accumulated biogas production. The evaluation of the methanogenic potential is part of a research project carried out with other institutions around the country, with the support of the Brazilian Agricultural Research Corporation (EMBRAPA). The current work can provide information on the optimization of the design and operation, however the production of methane using the substrate may vary according to the conditions and statistics studied.